2015
DOI: 10.1007/s10865-015-9663-0
|View full text |Cite
|
Sign up to set email alerts
|

Age, subjective stress, and depression after ischemic stroke

Abstract: The incidence of stroke among younger adults in the United States is increasing. Few studies have investigated the prevalence of depressive symptoms after stroke among different age groups or the extent to which subjective stress at the time of stroke interacts with age to contribute to post-stroke depression. The present study examined whether there exists an age gradient in survivors’ level of depressive symptoms and explored the extent to which financial, family, and health-related stress may also impact on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 58 publications
1
37
2
Order By: Relevance
“…13 Two studies included caregivers of survivors who were 60 years of age or older, 13,15 resulting in limited generalizability for survivors who are in early to mid-life and experiencing the unique stressors that accompany those life stages. 21 Six countries were represented (USA, 9,14,18 Canada, 10 UK, 11 Germany, 12,13 Netherlands, 16 Korea 15,17 ), many with drastically different healthcare systems and cultural norms around illness recovery and caregiving, raising further questions about generalizability; however, these studies provide a more global perspective.…”
Section: Resultsmentioning
confidence: 99%
“…13 Two studies included caregivers of survivors who were 60 years of age or older, 13,15 resulting in limited generalizability for survivors who are in early to mid-life and experiencing the unique stressors that accompany those life stages. 21 Six countries were represented (USA, 9,14,18 Canada, 10 UK, 11 Germany, 12,13 Netherlands, 16 Korea 15,17 ), many with drastically different healthcare systems and cultural norms around illness recovery and caregiving, raising further questions about generalizability; however, these studies provide a more global perspective.…”
Section: Resultsmentioning
confidence: 99%
“…After excluding duplicates, our combined searches identified a total of 11884 studies. A total of 29 studies (Aben et al, 2006;;Bara et al, (2016); Caeiro et al, 2006;Castellanos-Pinedo et al, 2011;De Ryck et al, 2013;Dou et al, 2015;Gillen et al, 2001;Hackett et al, 2006;Jorgensen et al, 2016;Kim et al, 2014;Kocer et al, 2011;Kootker et al, 2016;Liu et al, 2017;McCarthy et al, 2016;Ng et al, 1995;Paolucci et al, 2006;Pohjasvarra et al, 1998;Prisnie et al, 2016;Schottke et al, 2015;Sienkiewicz-Jarosz et al, 2010;Singh et al, 2000;Slater et al, 2012;Tang et al, 2005;Tang et al, 2011;Tse et al, 2017;Verdelho et al, 2004;Vermeer et al, 2017;White et al, 2014;Zhang et al, 2010 ) met our inclusion criteria (164993 patients; see Table 1). We requested additional data from seven authors and received data from one (Acknowledgements).…”
Section: Resultsmentioning
confidence: 99%
“…However, one study was removed from analysis due to a lack of symmetry of log values. (McCarthy et al, 2016) This left eight studies with a combined sample size of 37483 for meta-analysis. Random-effects analysis suggested a pooled odds ratio of 3.03 (95% CI of 2.30-3.98) ( Figure 5).…”
Section: Association With Post-stroke Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Family support has been reported as a protective factor for major depression in chronic diseases such as cancer [38]. Research has similarly shown that depressive symptoms are negatively correlated with social support [17]; thus, it is logical to suggest that stroke patients who do not have a spouse might be more depressed than those with a spouse.…”
Section: Discussionmentioning
confidence: 99%